Perancangan Lemari Multifungsi Untuk Rumah Tinggal - Christofer Chandra; Adi Santosa; Grace Setiati Kattu (Intra, 2019)
The fashion world is now experiencing rapid development, especially in Indonesia, because fashion is the part that cannot be separated from people’s appearance and everyday style, and also as a communication tool to state their identity. The development of fashion world also affects the emergence of manufacturers offering goods that have been designed to attract the attention of consumers to meet their fashion needs and be more up to date. Fashion needs they buy and also collect make the role of furniture very much needed to become a storage container at home. Therefore in this design multifunctional wardrobe are designed not only to store clothes, but also other items such as shoes, hats, bags, and other accessories based on collected data on user needs and activities while in a storage cabinet, so that the designed cabinets can store many items in the same place without having to be placed separately and also make user activities easier when selecting the items to be used.